Implementation of Profil Pelajar Pancasila in Civics Education learning at MAN 1 Medan - Nadiah Firza; Syarbaini Saleh (Curricula: Journal of Curriculum Development, 2025)
Civics Education subjects play a strategic role in instilling national values and shaping students' characters in the madrasah. However, the extent to which Proyek Penguatan Profil Pelajar Pancasila (P5) values are integrated into Civics Education learning and supported by teacher strategies remains unclear. This study aims to describe the implementation of strengthening the Profil Pelajar Pancasila through Civics Education learning in grades X and XI at MAN 1 Medan, as well as identifying supporting and inhibiting factors. This study employs a qualitative approach, utilizing a case study method. Informants were selected through purposive sampling, comprising main informants (the deputy head of the madrasah and Civics Education teachers), key informants (students), and supporting informants. Data were collected through interviews and documentation, and then analyzed using the Miles and Huberman interactive model. The analysis was tested for validity through triangulation and a member check. The results of the study indicate that P5 values have been integrated into the Civics Education learning contextually and collaboratively, supported by the madrasah environment and teacher role models. However, teacher understanding and student backgrounds are obstacles to its implementation. The implementation of P5 in civics learning has a positive impact on student character formation. Innovation in learning and teacher training is necessary to ensure the optimal and sustainable internalization of Pancasila values.   Abstrak Mata pelajaran Pendidikan Kewarganegaraan (PKN) memiliki peran strategis dalam menanamkan nilai-nilai kebangsaan dan membentuk karakter peserta didik di madrasah, namun hingga kini belum diketahui secara jelas sejauh mana integrasi nilai-nilai P5 dalam pembelajaran PKN dan strategi guru dalam mendukungnya. Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan penguatan Profil Pelajar Pancasila melalui pembelajaran PKN pada peserta didik kelas X dan XI di MAN 1 Medan, sekaligus mengidentifikasi faktor pendukung dan penghambatnya. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Informan dipilih secara purposive sampling meliputi informan utama (wakil kepala madrasah dan guru PKN), informan kunci (peserta didik), dan informan pendukung. Data dikumpulkan melalui wawancara dan dokumentasi, kemudian dianalisis menggunakan model interaktif Miles dan Huberman serta diuji keabsahannya melalui triangulasi dan member check. Hasil penelitian menunjukkan bahwa nilai-nilai P5 telah terintegrasi dalam pembelajaran PKN secara kontekstual dan kolaboratif, didukung lingkungan madrasah dan keteladanan guru. Namun, keterbatasan pemahaman guru dan latar belakang peserta didik menjadi hambatan dalam implementasinya. Implementasi P5 dalam pembelajaran PKN berdampak positif terhadap pembentukan karakter peserta didik. Diperlukan inovasi pembelajaran dan pelatihan guru agar internalisasi nilai Pancasila lebih optimal dan berkelanjutan. Kata Kunci: karakter peserta didik; Kurikulum Merdeka; pendidikan Kewarganegaraan; profil pelajar Pancasila